THE ROLE OF THE HADITHS OF THE PROPHET MUHAMMAD (PEACE BE UPON HIM) IN YOUTH EDUCATION AND THE CONTEMPORARY PEDAGOGICAL PROCESS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the interrelationship between education and upbringing, as well as the pedagogical significance of national and religious values in the spiritual and moral development of the younger generation. It analyzes the responsibilities of families and educational institutions in raising children and addresses the formation of good manners, patriotism, humanism, national pride, and civic responsibility. The article also explores opportunities for developing students’ independent thinking, creativity, and spiritual resilience through the hadiths of the Prophet Muhammad (peace be upon him), the educational views of prominent thinkers, and modern pedagogical technologies. Furthermore, it substantiates pedagogical approaches to strengthening cooperation between teachers and students and protecting young people from the negative effects of globalization and the contemporary information environment.